Hydroisomerization of Sudanese Light Naphtha Over Improved Beta(Pt/H-β Co-Crystalline) Zeolite Catalyst - Albegali, Fekri M.; Abdalla, Babiker K.; Mahajoub, Imad E. A. (Gezira Journal of Engineering and Applied Sciences, 2018)
The hydroisomerization of light paraffins is an important industrial process to obtain branched alkanes, which are used as octane boosters in gasoline. The Sudanese light naphtha (Produced in Khartoum Refinery) was chosen as the case study in this paper. The aims of this study were to produce isomers that high octane number. Type Beta Zeolite Improved (Pt/H-β Co-Crystalline), catalyst was prepared, with 0.5wt% (H 2 PtCl 6 .6H 2 O) by impregnation method. The hydroisomerization unit was constructed from copper blossom and designed to carry out the hydroisomerization process. The fixed bed reactor dimensions were OD 3.5cm, ID 1cm, reactor total volume 22.765 cm 3 and 30cm length. All experiments were made at atmospheric pressure and reaction temperature of 160°C. The results show that the conversion of the main light naphtha components to (n-C 4 ,isopentane, n-C 5 , 2,2DMC 4 ,3MC 5 ), at 160°C. Also, it was noted that the selectivity to isomers over improved Beta (Pt/H-β Co-Crystalline) Zeolite increases at temperature 160°C. The orginal light naphtha gives Research Octane Number (RON 67.49) and the light naphtha over Beta (Pt/H-β Co-Crystalline) Zeolite catalyst gives (RON 89.52) which is a very good result.